2022
DOI: 10.1186/s40479-022-00197-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Estonian version of the Semi-structured Interview for Personality Functioning DSM-5 (STiP-5.1)

Abstract: Background The DSM-5 Alternative Model for Personality Disorders introduced a dimensional perspective on personality disorders. The model assesses functioning in four domains: Identity, Self-Direction, Empathy, and Intimacy. This study evaluates the psychometric properties of the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1) in Estonian. Method The sample consists of 131 participants: 58 from the general population and 73 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…This assertion also aligns with specific requirements from individual elements to assign a specified PD in the AMPD. Regardless, although debate regarding the factor structure of Criterion A is ongoing [ 67 ], the two-factor component reflecting self- and interpersonal functioning, aligns with previous research (mostly in adults) on Criterion A that, despite some mixed results, has mostly found a two-factor structure (resembling self- and interpersonal-functioning) to be most appropriate [ 26 , 68 , 69 ]. Thus, the supporting two-factor component might reflect the broader developmental applicability and suitability of the LPFS in assessing personality pathology across the life course, whereby the structure of self- and interpersonal-functioning is retained in both adult and adolescent samples.…”
Section: Discussionsupporting
confidence: 56%
“…This assertion also aligns with specific requirements from individual elements to assign a specified PD in the AMPD. Regardless, although debate regarding the factor structure of Criterion A is ongoing [ 67 ], the two-factor component reflecting self- and interpersonal functioning, aligns with previous research (mostly in adults) on Criterion A that, despite some mixed results, has mostly found a two-factor structure (resembling self- and interpersonal-functioning) to be most appropriate [ 26 , 68 , 69 ]. Thus, the supporting two-factor component might reflect the broader developmental applicability and suitability of the LPFS in assessing personality pathology across the life course, whereby the structure of self- and interpersonal-functioning is retained in both adult and adolescent samples.…”
Section: Discussionsupporting
confidence: 56%
“…The STiP5.1 has been translated into several versions and proven to be valuable to evaluate personality functioning dimensions. Notably, it has been utilized effectively in different cultural contexts, such as the Czech [55], Estonian [56], and German [57] versions. As a specific tool for assessing personality functioning in adolescence, the Levels of Personality Functioning Questionnaire 12-18 (LoPF-Q 12-18) is available and recommended [58].…”
Section: Measures Of Severitymentioning
confidence: 99%
“…Administered in 45 min on average, it may also contribute to participant burden (Weekers et al, 2021). Moreover, this interview-based measure is, to our knowledge, thus far validated in Dutch, Czech, Estonian, and German samples (Heissler et al, 2021;Oitsalu et al, 2022;Wang & Eastwick, 2020;Zettl et al, 2019). As a result, there is a need for briefer, more time-efficient LPF measures that can be used in English-speaking countries and that are validated for adolescents.…”
mentioning
confidence: 99%